STUDY ON THE EFFECT OF ALGINATE, TYPE OF CROSS LINKERS, AND MUCOADHESIVE POLYMERS ON DRUG RELEASE FROM LOVASTATIN-LOADED MUCOADHESIVE CROSS-LINKED MICROBEADS - VENKATA RAMANA REDDY K; NAGABHUSHANAM MV (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The aim of the current study is to prepare and lovastatin-loaded alginate microbeads were prepared using emulsification gelation internal method by the use of different cross-linking agents, polymer effect in different concentrations on drug release and its combination with hydrophilic polymers on drug release. Methods: The effect of sodium alginate concentration and its combination with other hydrophilic polymers on particle size and shape, scanning electron microscopy (SEM) studies, entrapment efficiency, Fourier transform infrared (FTIR) analysis (FTIR), differential scanning calorimetry (DSC) studies, and X-ray diffraction (XRD) studies conducted to determine compatibility of drug and used excipients and in vitro drug release was studied. The efficiency of mucoadhesion strength of microbeads is determined by wash-off study. Results: The optimum condition for preparation alginate beads and produces sustained release manner was occurred at 3% polymer mixture. Infrared spectroscopic study confirmed the presence of compatibility between drug-polymer additives, good drug entrapment, and SEM studies prove microbeads were in spherical and rough particles. XRD and DSC were used to confirm successful entrapment of drugs into the alginates microbeads. The in vitro release profile could be altered notably by changing formulation parameters to give a sustained release of drug from the microbeads. Conclusion: The kinetic modeling of the release data indicate that drug release from the microbeads follow anomalous transport mechanism and super Case-II transport mechanism and drug release is controlled by both swelling and relaxation of the polymer chains. The release of drug from formulation is pH dependent. This will help in overcoming the drawbacks of lovastatin with a short half-life, improves the bioavailability. The release kinetics of drug from the alginate beads followed zero order.